Identification of TMEM100’s role in immune infiltration regulation and construction of an endogenous RNA network in prostate cancer through pan-cancer analysis - Yinfeng Jiang; Tingan Pan; Zhenglin Zhang (Discover Oncology)
Abstract Background Prostate adenocarcinoma (PRAD) is a prevalent urinary tumor with an elusive etiology. While transmembrane protein 100 (TMEM100) plays diverse roles in various cancers, its involvement in prostate cancer remains unexplored. Herein, we aim to elucidate the impact of TMEM100 on prostate cancer diagnosis and progression. Methods Utilizing data from the TCGA database, we analyzed mRNA sequences, clinical information, and methylation data. Prognostic analysis was conducted using the GEPIA database, and a nomogram was developed using the “rms” package in R software. Drug sensitivity was assessed using the “pRRophetic” package. The correlation between TMEM100 and immune infiltration was investigated using the TIMER and TISDIB databases. Methylation levels were evaluated using Perl and R software. The competitive endogenous RNA (ceRNA) network was constructed using the starBase database. Functional assays including qRT-PCR, CCK8, EdU, and IHC assays were employed to evaluate TMEM100’s role in PRAD. Results TMEM100 expression was significantly reduced in prostate cancer tissues compared to normal tissues, correlating with poor prognosis in PRAD. The multivariable model nomogram demonstrated enhanced prediction of PFI. Additionally, the low-expression TMEM100 group exhibited lower IC50 values for several chemotherapy drugs. TMEM100 was closely associated with various immune cell types, immunomodulators, and chemokines, exerting anti-tumor effects. Higher methylation levels of TMEM100 were observed in PRAD, with specific CpG sites showing significant correlation. TMEM100 hypermethylation correlated with immune infiltration in PCa. Furthermore, a TMEM100-related ceRNA network was constructed in PRAD, corroborating TMEM100’s role in PCa through functional experiments. Conclusion TMEM100 downregulation, through modulation of immune infiltration and epigenetic mechanisms, correlates with poor prognosis and tumor cell proliferation in PRAD.